Availability of a smartphone version of eGENA, the German digital cognitive aid for crisis management in anaesthesiology - Richter, T.; Baus, J.; Eismann, H.; Happel, O.; Heller, A. R.; Neuhaus, C.; Weinert, M.; St. Pierre, Michael (Anästhesiologie & Intensivmedizin, 2021)
The German Cognitive Aid Working Group of the Professional Association of German Anaesthesiologists (BDA) and the German Society of Anaesthesiology and Intensive Care Medicine (DGAI) developed 'eGENA', a browser-based cognitive aid for intra- and postoperative emergencies using an iterative user-centred design process according to DIN EN ISO 9241-210. The app is available for free download.
CRIS-Team WoS Importer:2021-08-27